Paradigms in cryptology -- Mycrypt 2016 : malicious and exploratory cryptology : second International Conference, Mycrypt 2016, Kuala Lumpur, Malaysia, December 1-2, 2016, Revised selected papers /: malicious and exploratory cryptology : second International Conference, Mycrypt 2016, Kuala Lumpur, Malaysia, December 1-2, 2016, Revised selected papers. (2017) - Unknown
No abstract available